Reason and Rationality during Energy Crises - Daly, George G.; Mayor, Thomas H. (Journal of Political Economy, 1983)
This paper develops a technique for extracting the expectations embedded in the current prices of energy-using durable goods and applies it to used car markets during the two energy "crises" of the 1970s. The resulting estimates indicate that consumers took the energy crises seriously and formed expectations about future gasoline prices that appear rational when compared with the historical gasoline price series, with the forecasts of specialists and experts, or with the actual postsample behavior of gasoline prices. The evidence therefore supports the view that consumers are able to make rather complex choices with a great deal of rationality and casts doubt on the wisdom of policies based on assumptions to the contrary.